IVIG for refractory dysphagia in Antisynthetase syndrome: A truth hard to swallow. Issue 11 (13th November 2022) - Alnoukari, Mais; De La Garza, Oziel Garza; Al Gburi, Karrar; Patel, Niral; Lopez, Henderson; Shamim, Muhammad; Kwang, Henry
Abstract: Refractory dysphasia could be the main symptom of Antisynthetase syndrome (ASS). IVIG may have a major impact in the successful treatment of dysphasia in patients with ASS. In our patient with ASS, IVIG treatment was an unreplaceable treatment option, and the patient regains her ability to swallow within 2 days. Abstract : Refractory dysphasia could be the main symptom of Antisynthetase syndrome (ASS). IVIG may have a major impact in the successful treatment of dysphasia in patients with ASS. A cure can be possible within just 2 days of IVIG treatment.